2005
DOI: 10.1159/000082787
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment after Stroke – Impact on Activities of Daily Living and Costs of Care for Elderly People

Abstract: Background and Purpose: The economic burden of stroke is substantial and is likely to increase with an increasing number of elderly individuals in the population. There is thus a need for information on the use of health care resources and costs among these elderly stroke patients. We examined the impact of the cognitive impairments on the ability to perform activities of daily living (ADL) and utilization and costs of health care in a cohort of elderly stroke patients. Methods: One hundred and forty-nine pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 44 publications
6
84
1
3
Order By: Relevance
“…To be able to return to work is also a key factor for subjective well-being and life satisfaction [40]. Moreover, in a study in which ability to independently carry out daily living activities was evaluated in elderly patients with stroke, it was found that for patients with cognitive impairment, the costs were three times higher compared to those without cognitive impairments [41].…”
Section: Discussionmentioning
confidence: 99%
“…To be able to return to work is also a key factor for subjective well-being and life satisfaction [40]. Moreover, in a study in which ability to independently carry out daily living activities was evaluated in elderly patients with stroke, it was found that for patients with cognitive impairment, the costs were three times higher compared to those without cognitive impairments [41].…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in cognitive functioning post-stroke are strongly associated with a person's ability to carry out tasks of daily living (ADLs) and an ability to live independently, regardless of the person's physical ability (Claesson, Linden, Skoog & Blomstrand, 2005;Nys et al, 2005c A test used for diagnosis or screening should have good diagnostic validity, i.e.…”
Section: Referencementioning
confidence: 99%
“…El deterioro cognitivo secundario a un ictus se asocia con una mayor mortalidad (Tatemichi et al, 1994), mayor tasa de institucionalización (Pasquini, Leys, Rousseaux, Pasquier, y Henon, 2007) y un aumento en los costes sanitarios (Claesson, Linden, Skoog, y Blomstrand, 2005). Reducir el impacto de la HVE en la capacidad funcional del paciente debe ser uno de los objetivos de la rehabilitación del ictus ya que influye directamente en su calidad de vida, así como la de sus cuidadores.…”
Section: Conclusionesunclassified